ANATOMICAL VARIATIONS OF VERTEBRAL ARTERY - A CADAVERIC STUDY WITH CLINICAL RELEVANCE - Dr Amudalapalli S Narayana,; Dr Ashok Aenumulapalli,; Dr Kiran Kumar P,; Dr Anitha T, (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Introduction: Vertebral arteries originate from the root of the neck as the first branches from the superior-posterior aspect of the subclavian arteries. The VA typically gives off spinal, muscular, meningeal branches, the anterior spinal artery, ramus choroideus ventriculi quarti, medial and lateral medullary branches and the terminal branch, the posterior inferior cerebellar artery (PICA). Material and methods: An observational cadaveric study was conducted on 30 formalin-fixed human cadavers from 2022 to 2025 in the Department of Anatomy, Chalmeda Anandarao institute of medical sciences, Karimnagar, Telangana, India.Results: Variations were found in the origin and course of vertebral artery in our study. Variations in the origin of vertebral artery were found in four cases (6.6%) out of 30 cadavers, 60 vertebral arteries are examined. The Left Vertebral artery was arising directly from the arch of aorta instead of arising from Subclavian artery in four cases (6.6%). Variation in the course of vertebral artery was found in one case (1.6%).  Left vertebral artery was entering into the foramen transversarium of C3 vertebra instead of C6.Discussion: The left vertebral artery arising directly from arch of aorta between left common carotid and left subclavian arteries which accounts to about 2.4-5.8 percent of cases. In most occasions the LVA emerged between the left common carotid artery (LCCA) and the left subclavian artery (LSCA). The LVA varies in origin more than the right.  Conclusion: Vertebral artery and its variations is of great importance for the planning of aortic arch surgery or endovascular intervention and prevention of vascular complications during minimally invasive diagnosis and treatment of cerebral vascular diseases.